(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The importance of research is to be considered by highlighting the tax policy in Iraq which extended for successive measurement of the amount of tax receipts for respective periods, the research problem represents security, economic and political issues that Iraq suffered which were very difficult since Nineties of the last century until now that led to a lake of clarity in tax policy trends, volatility in it and finally reflected on the tax revenues increase or decrease. One of the main recommendations of the research is: (The necessity to develop a deliberate strategy for tax policy in Iraq which should take into account financial, economic, and social goals in appropriate way).